Strong Convergence Theorems for the Generalized Split Common Fixed Point Problem - Cuijie Zhang (Journal of Applied Mathematics)
We introduce the generalized split common fixed point problem (GSCFPP) and show that the GSCFPP for nonexpansive operators is equivalent to the common fixed point problem. Moreover, we introduce a new iterative algorithm for finding a solution of the GSCFPP and obtain some strong convergence theorems under suitable assumptions.